2020
DOI: 10.1088/1755-1315/423/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable food agriculture land protection policy for Gunungkidul, Yogyakarta, Indonesia: solution or dilemma?

Abstract: Climate change has an impact on the environment, especially in agriculture. Climate change which caused the emergence of extreme weather led to declining agricultural productivity or crop failures in several regions. Some areas of Gunungkidul are the most difficult areas to plant rice compared to other regencies/cities in the Special Region of Yogyakarta. The issue of agricultural land conversion is a problem for almost all countries in the world that are difficult to resolve as development increases. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…by a prohibition on dividing the land into parts that are too small (less than 2 ha) Article 17 paragraph (1) and paragraph (4) of Law Number 5 of 1960 respecting Basic Agrarian Regulations, often known as the Basic Agrarian Law (UUPA), govern the minimum area of land ownership (1), taking into account the provisions in Article 7, where to achieve the objectives referred to in Article 2 paragraph (3), the maximum and or minimum land ar (4) The achievement of the minimum limit referred to in paragraph (1) of this article, which will be determined by legislation, will "Transfer of rights to agricultural land, except for inheritance distribution, is banned if the transfer leads in the emergence or continuance of land ownership with an area of fewer than two hectares." If the seller merely possesses a parcel of property with a total size of fewer than 2 hectares and all of the lands are sold, this prohibition does not apply.…”
Section: Rules Regarding the Limitation Of The Minimum Area Of Agricu...mentioning
confidence: 99%
See 3 more Smart Citations
“…by a prohibition on dividing the land into parts that are too small (less than 2 ha) Article 17 paragraph (1) and paragraph (4) of Law Number 5 of 1960 respecting Basic Agrarian Regulations, often known as the Basic Agrarian Law (UUPA), govern the minimum area of land ownership (1), taking into account the provisions in Article 7, where to achieve the objectives referred to in Article 2 paragraph (3), the maximum and or minimum land ar (4) The achievement of the minimum limit referred to in paragraph (1) of this article, which will be determined by legislation, will "Transfer of rights to agricultural land, except for inheritance distribution, is banned if the transfer leads in the emergence or continuance of land ownership with an area of fewer than two hectares." If the seller merely possesses a parcel of property with a total size of fewer than 2 hectares and all of the lands are sold, this prohibition does not apply.…”
Section: Rules Regarding the Limitation Of The Minimum Area Of Agricu...mentioning
confidence: 99%
“…If the seller merely possesses a parcel of property with a total size of fewer than 2 hectares and all of the lands are sold, this prohibition does not apply. (2): if two or more people own less than 2 hectares of land within one year, it is mandatory to appoint one who will own the land or transfer it following paragraph (1). Suppose those referred to in paragraph (2) of this article fail to meet their obligations.…”
Section: Rules Regarding the Limitation Of The Minimum Area Of Agricu...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the local government anticipates under the national policy through the Protection of Sustainable Food Agricultural Land (PLP2B) policy, although the implementation is not fully running optimally. For example, a research (Anggalini et al, 2020) in Gunung Kidul, Yogyakarta showed that the performance of policy implementation (PLP2B) was not optimal. Stagnation in planning and implementation activities also affects the performance of other activities.…”
Section: Literature Reviewmentioning
confidence: 99%